Compilations in local government organization - Geduspan, Jona (University of the Philippines Visayas, 2012)
Today, Local Government Units (LGU) are confronted with many challenges in the political, economic, technological, and geographical environment. In order to perform the public functions and services required to LGUs effectively and efficiently, leaders must initiate excellent management practices and innovations to address these challenges. Leaders must formulate appropriate mission and vision for their respective LGU, organize its resources properly to achieve its goals and objectives, direct, motivate, and develop its human capital, and evaluate and control the actions and plans implemented. They must also explore and use the available options of the LGU according to law to obtain the necessary resources to materialize its mission and vision. The objective of this paper is to develop the understanding and promote critical thinking f graduate students towards LGUs. The study features the local government unit which is the Municipality of Guimbal, evaluating its organizational structure, analyzing the effectiveness and efficiency of devolution of powers, identifying its sources of income, determining how its resources were spent last year by identifying the programs and projects implemented, assess the relationship of the LGU with other government agencies, and present the current best practice of the LGU which is its active Disaster Management System. This paper also includes a description of the distinct attributes of the special regions in the Philippines, namely, the Autonomous Region in Muslim Mindanao (ARMM) and Cordillera Administrative Region (CAR). Moreover, the researchers also gave their analysis and evaluation about the implementation of the Municipality of Dumangas of its Climate Field School Program, which addresses food security and disaster risk reduction in the community. The researchers were able to witness also the conduct of the General Assembly Meeting of Barangay Sto. Domingo in the district of Arevalo, Iloilo city and gave n assessment and recommendations about the accomplishment and future plans of the said barangay. The researchers believe that this study id useful especially in managing Local Government Units to achieve sustainable development. Leaders of LGUs must recognize the importance of commtted and honest governance in delivering public services through exploring innovations and promoting cooperation and partnership among their respective constituents and other private and civic organizations.